DURABILTY OF 25 LOCAL SPECIFIC WOOD SPECIES FROM JAVA PRESERVED WITH CCB AGAINST MARINE BORERS ATTACK - Mohammad Muslich; Sri Rulliaty (Indonesian Journal of Forestry Research, 2010)
This study was conducted to provide basis information of the 25 local specific wood species indigenous from Java treated by copper bichromated boron (CCB). The full-cell process for 2 hours and 150 psi during the pressure-keeping period was employed. The IUFRO method was applied for the determination of wood treatability class. The treated and untreated wood specimens were tied together using plastic cord, arranged into a raft like assembly, and then exposed for 3, 6, and 12 months to the brackish water situated at Rambut Island’s coastal area. The Nordic Wood Preservation Council (NWPC) standard No.1.4.2.2/75 was used to determine the intensity of marine borer infestation. The results revealed that 19 out of those 25 species were classified as easy to be preser ved, four species as moderate, and the remaining two were difficult to be preser ved. Those 19 species, i.e. Tamarindus indica L., Diplodiscus sp., Ficus variegate R .Br., Ehretia acuminata R .Br., Meliocope lunu-ankenda (Gaertn) T.G. Hartley, Colona javanica B.L., Pouteria duclitanBachni., Stercularia oblongata R .Br., Ficus vasculosa Wall ex Miq., Callophyllum grandiflorum JJS., Turpinia sphaerocarpa Hassk., Neolitsea triplinervia Merr., Acer niveum Bl., Sloanea sigun Szysz., Castanopsis acuminatissima A.DC., Cinnamomum iners Reinw. Ex Blume., Litsea angulata Bl., Ficus nervosa Heyne., and Horsfieldia glabra Warb. were more permeable implying that the CCB retention and penetration were greater and deeper. Hymeneaecarboril.L., LitseaodoriferaVal., Gironniera subasqualisPlanch., and LinderapolyanthaBoerl. were moderately permeable. Castanopsis tunggurut A.DC. and Azadirachta indica Juss. were the least permeable judging that the CCB retention and penetration were lowest and shallowest. The treated wood specimens in this regard were able to prevent marine borers attack. Meanwhile, the untreated specimens were susceptible to marine borers attack, except Azadirachta indica. The attacking borers consecutively are MartesiastriataLinne that belongs to the Pholadidae family ; and Teredo bartschi Clapp., Dicyathifer manni Wright., and Bankia cieba Clench. to the Terdinidae family.